(untitled) (The Pakistan Development Review, 2014)
Energy inflation has remained a significant topic in macroeconomic policy for the past few decades. This is due to several reasons pertaining to both demand and supply sides. In addition, the history of energy prices has also been characterised by extreme volatilities, Hamilton (2008). This makes forecasting and modelling of energy prices difficult, nevertheless it is important to model and forecast energy prices in all economies. In this paper we have tried to identify the determinants of energy inflation in Pakistan. Energy products are a critical component in any economy, serving as a core input, particularly in manufacturing industries. Moreover, the demand for energy and fuel comes from households fuelling cars and kitchens for which other alternatives are not easily available. This renders the demand inelastic compared to any other good [Edelstein and Kilian (2009)], making economies vulnerable to supply and price shocks. The energy price inflation therefore through cost push inflation and demand-pull inflation has a major impact on core inflation itself, thereby playing a significant role in macroeconomic health of a country. As predicted by Ben Bernanke for the US in 2006, “in the long run energy prices can reduce the productive capacity of US economy if high energy costs make businesses less willing to invest new capital”. The nature of the energy market itself creates a major gap between the oil consumers and oil producers. Whilst demand is inelastic everywhere, supply is limited and is difficult to increase, and confined to certain regions on Earth. This is true particularly for two of the most common energy types: oil and gasoline. The supply of oil is controlled by a few countries, and supply shocks therefore lead to an immediate surge in prices.